The diagnostic and prognostic value of growth differentiation factor‐15 in systemic lupus erythematosus‐associated pulmonary arterial hypertension - Qian, Junyan; Ding, Yufang; Yang, Xiaoxi; Wang, Qian; Zhao, Jiuliang; Liu, Yongtai; Tian, Zhuang; Wang, Yanhong; Li, Mengtao; Zeng, Xiaofeng (Pulmonary circulation, 2023)
Growth‐differentiation factor (GDF)‐15 is a member of transforming growth factor‐β‐related cytokine and may respond to right ventricular overload. The objective of this article was to assess the diagnosis and prognostic value of GDF‐15 in systemic lupus erythematosus‐associated pulmonary arterial hypertension (SLE‐PAH). Serum samples were obtained from 65 patients with SLE‐PAH, 51 sex and age matched patients of SLE without PAH (SLE‐non‐PAH), and 32 healthy controls. Serum GDF‐15 level was detected by enzyme‐linked immunosorbent assay and the optimal cut‐off point was determined by receiver operating characteristic curve. The primary end‐point was death from any cause and the secondary end‐point was target goal achievement (TGA). Cox regression analyses and Kaplan−Meier method were performed to identify the prognostic value of GDF‐15. Serum GDF‐15 levels were significantly higher in SLE‐PAH patients (1112.14 ± 781.80 pg/mL) than SLE‐non‐PAH patients (810 ± 408 pg/mL) and healthy controls (442 ± 139 pg/mL) at baseline. The optimal cut‐off value of GDF‐15 in the diagnosis of SLE‐PAH was 733 pg/mL (AUC = 0.84). In patients with SLE‐PAH, GDF‐15 level was associated with 6 min walking distance (ρ = −0.385, p = 0.017) and higher serum N terminal‐pro brain natriuretic peptide (NT‐proBNP) (ρ = 0.605, p < 0.001). Patients with GDF‐15 > 733 pg/mL were more likely to death (adjusted hazard ratio [HR] = 4.01, 95% confidence intervals [CI]: 1.23−6.27, p = 0.041) and less likely to achieve treatment goal (adjusted HR = 0.57, 95% CI: 0.23−0.79, p = 0.028). In addition, patients with simultaneous elevation of GDF‐15 and NT‐proBNP showed lower proportion of TGA (p = 0.046). In conclusion, GDF‐15 is a new and promising biomarker of development and prognosis in SLE‐PAH. The combination of GDF‐15 and NT‐proBNP may provide more accurate prognostic information.